2014
DOI: 10.1056/nejmoa1308851
|View full text |Cite
|
Sign up to set email alerts
|

Mutant ZP1 in Familial Infertility

Abstract: Summary The human zona pellucida is composed of four glycoproteins (ZP1, ZP2, ZP3, and ZP4) and has an important role in reproduction. Here we describe a form of infertility with an autosomal recessive mode of inheritance, characterized by abnormal eggs that lack a zona pellucida. We identified a homozygous frameshift mutation in ZP1 in six family members. In vitro studies showed that defective ZP1 proteins and normal ZP3 proteins colocalized throughout the cells and were not expressed at the cell surface, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 25 publications
5
98
2
2
Order By: Relevance
“…This mutation was absent in our in‐house ethnic‐matched 2,200 individual genomes and the public databases including 1000 Genome, ExAc database, and ESP6500 database. Interestingly, the second heterozygous mutation, a frameshift deletion of 8 nt, c.1169_1176del (p.I390Tfs*16), in exon 7 of ZP1 (Refseq: NM_207341.3), transmitted from the mother of the proband (Figure a, I‐2 and 1h), was the same mutation reported by a previous work (Huang et al, ). In that work, Huang et al found in a familial infertility case a homozygous mutation, caused a premature stop codon (I390fs404X), which resulted in a truncated protein of 404 amino acids, instead of the 638‐amino‐acid original ZP1 protein (Figure g), posited that the defective ZP1 hindered the transportation of ZP3, another key element in zona pellucida, from the cytoplasm to the surface of oocyte (Huang et al, ).…”
Section: The Art Cycles Descriptionsupporting
confidence: 79%
See 1 more Smart Citation
“…This mutation was absent in our in‐house ethnic‐matched 2,200 individual genomes and the public databases including 1000 Genome, ExAc database, and ESP6500 database. Interestingly, the second heterozygous mutation, a frameshift deletion of 8 nt, c.1169_1176del (p.I390Tfs*16), in exon 7 of ZP1 (Refseq: NM_207341.3), transmitted from the mother of the proband (Figure a, I‐2 and 1h), was the same mutation reported by a previous work (Huang et al, ). In that work, Huang et al found in a familial infertility case a homozygous mutation, caused a premature stop codon (I390fs404X), which resulted in a truncated protein of 404 amino acids, instead of the 638‐amino‐acid original ZP1 protein (Figure g), posited that the defective ZP1 hindered the transportation of ZP3, another key element in zona pellucida, from the cytoplasm to the surface of oocyte (Huang et al, ).…”
Section: The Art Cycles Descriptionsupporting
confidence: 79%
“…The model of zona pellucida development includes intraplasmic synthesis and maturation of the component proteins, transportation to the cell surface, and interweaving among the four ZP proteins (Huang et al, ). Among this process, ZP1 plays a critical role which cross‐links the long chains of filaments made of consecutive alternates of ZP2, ZP3, and ZP4.…”
Section: The Art Cycles Descriptionmentioning
confidence: 99%
“…Previously, Huang et al identified a homozygous frameshift mutation of ZP1 (MIM: 195000) inherited in recessive fashion from a family exhibiting oocytes devoid of a ZP. 20 The frameshift mutation formed a premature stop codon and resulted in a truncated ZP1, which was postulated to sequester ZP3 in the cytoplasm and prevent the formation of a ZP by working in loss-of-function way. In our study, the heterozygous p.Ala134Thr substitution in ZP3 impeded the interaction between ZP3 and ZP2 and eventually led to oocyte degeneration, by working in a dominantnegative way.…”
Section: Efs Can Be Classified As Either False Efs (Fefs) or Genuine mentioning
confidence: 99%
“…Presence of ZP2 (A) and ZP4 (B) transcripts was evaluated by RT-qPCR analysis MFCS = oocytes isolated from medium follicles of cycling sows, SFJG = oocytes from small follicles of juvenile gilts, SFCS = oocytes from small follicles of cycling sows Results are presented as mean ± SEM with the level of significance of P < 0.001 (*P < 0.01) a-c values with different superscripts are significantly different secondary sperm receptors, playing a significant role in gamete fusion during successful monospermic fertilization (Topfer-Petersen 1999). It has been previously shown in several species that oocytes lacking ZPs proteins are unable to fertilize (Harada et al 2003;Wassarman and Litscher 2012;Huang et al 2014). Ovarian follicle size significantly influences the ability of oocytes to mature and the gamete fertilizability.…”
Section: Discussionmentioning
confidence: 99%